Efficacy and Safety of Zolpidem for Focal Dystonia After Neurosurgical Treatments: A Retrospective Cohort Study - Horisawa, Shiro; Kohara, Kotaro; Ebise, Hiroki; Nishitani, Masahiko; Kawamata, Takakazu; Taira, Takaomi (Frontiers in Neurology, 2022)
Although there are several reports of the significant efficacy of zolpidem for treating dystonia, zolpidem is still considered an anecdotal treatment. Here, we evaluated the efficacy and safety of zolpidem for treating residual dystonia in patients who previously received various neurosurgical treatments majorly including deep brain stimulation and radiofrequency ablation. We retrospectively reviewed medical records from January 2021 to September 2021 to identify patients with dystonia who had been prescribed zolpidem after undergoing neurosurgery. Twenty patients were enrolled in this study, including those with blepharospasm (two), tongue dystonia (four), mouth dystonia (one), spasmodic dysphonia (two), cervical dystonia (six), focal hand dystonia (three), hemidystonia (two), blepharospasm with cervical dystonia (one), and mouth dystonia with cervical dystonia (one). Single doses of zolpidem ranged between 2.5 and 10 mg, while daily dosages ranged from 10 to 30 mg. The zolpidem dose prescribed was 5–10 mg, with single and daily doses of 7 ± 2.9 and 14.5 ± 6.0 mg, respectively. With zolpidem administration, the participants' Burke-Fahn-Marsden Dystonia Rating Scale-Movement Scale score significantly improved from 8.1 ± 6.7 to 3.7 ± 2.5 (50.6% improvement, p < 0.0001). Improvements in arm dystonia, blepharospasm, and spasmodic dysphonia were observed using the Arm Dystonia Disability Scale, Jankovic Rating Scale, and Voice Handicap Index, respectively. No improvements were observed in cervical dystonia on the Toronto Western Spasmodic Torticollis Rating Scale. Drowsiness, including three cases each of mild and moderate drowsiness, was the most frequent adverse effect (30%), which persisted for 2–3 h. Transient amnesia and rapid eye movement sleep behavior disorder occurred in two patients and one patient, respectively. Although our findings suggest that zolpidem can be a valuable treatment option for patients with residual dystonia after neurosurgical treatments, the beneficial effects for cervical dystonia were limited.